Bioinoculants: A sustainable alternative to agrochemicals - Raj, Aman; Kumar, Adesh (Indian Farming, 2025)
Modern agriculture has heavily relied on synthetic agrochemicals to boost crop productivity, leading to significant increases in agricultural output. However, the widespread use of these chemicals had detrimental effects on the environment. Soil degradation, erosion, water contamination, and pesticide resistance are a few of those problems. Bioinoculants include a range of microorganisms with different properties and abilities that provide a sustainable solution to these problems. Rhizobium spp., Azospirillum spp., etc. act as plant growth-promoting rhizobacteria and play a key role in nutrient assimilation within the soil and from the environment through the nitrogen fixation process. On the other hand, Trichoderma spp., Pseudomonas spp., etc. play a crucial role in plant disease management. This article focuses on the role of bioinoculants in promoting overall plant growth with a focus on their application methods, dosage, performance on crops, challenges, and the current market trends in India.